Reimagining Mental Health through the Indian Knowledge System: Integrating Indigenous Wisdom with Contemporary Psychological Practice - D. Anuroopa; Uma G (Journal of Psychology and Social Sciences, 2026)
Mental health disorders have emerged as a profound global public health challenge, with escalating rates of anxiety, depression, professional burnout, loneliness, and emotional distress underscoring the necessity for holistic and culturally responsive therapeutic paradigms. The Indian Knowledge System (IKS) presents a comprehensive civilizational framework that conceptualizes human well-being through dynamic harmony across bodily, cognitive, ethical, and existential dimensions, rooted in classical texts including the Vedas, Upanishads, Bhagavad Gita, Patanjali’s Yoga Sutras, and Ayurveda. This qualitative review evaluates the integration of IKS constructs into modern clinical practice through secondary data analysis of empirical literature, public health reports, and theoretical texts. Key constructs—such as Triguna personality theory, Tridosha physiological regulation, Dharma, Abhyasa, Vairagya, and Sakshi Bhava—are critically analyzed and mapped alongside contemporary psychological frameworks, including Cognitive Behavioral Therapy (CBT), Mindfulness-Based Interventions (MBIs), Acceptance and Commitment Therapy (ACT), positive psychology, and neuroplasticity. The synthesized evidence demonstrates that IKS practices (pranayama, dhyana, Ayurvedic lifestyle regulation) foster autonomic balance, cognitive defusion, emotional resilience, and stress reduction. A four-level integrative mental healthcare model spanning preventive, therapeutic, community, and research domains is proposed. While promising, successful integration demands rigorous empirical standardization, interdisciplinary collaboration, ethical adaptation, and public policy alignment to deliver accessible, decolonized mental health interventions.